The role of type 2 innate lymphoid cells in eosinophilic asthma. Issue 4 (7th May 2019) - Salter, Brittany M; Aw, Michael; Sehmi, Roma
Abstract: Eosinophilic asthma has conventionally been proposed to be a T helper 2 driven disease but emerging evidence supports a central role of type 2 innate lymphoid cells (ILC2s). These are non-T, non-B cells that lack antigen specificity and produce more IL-5 and IL-13 than CD4 + T lymphocytes, on a cell per cell basis, in vitro. Although it is clear that ILC2s and CD4 + T cells work in concert with each other to drive type 2 immune responses, kinetic studies in allergic asthma suggest that ILC2s may act locally within the airways to "initiate" eosinophilic responses, whereas CD4 + T cells act locally and systemically to "perpetuate" eosinophilic inflammatory responses. Importantly, ILC2s are increased within the airways of severe asthmatics, with the greatest number of IL-5 + IL-13 + ILC2s being detected in sputum from severe asthmatics with uncontrolled eosinophilia despite high-dose steroid therapy. Although the precise relationship between ILC2s and steroid sensitivity in asthma remains unclear, controlling the activation of ILC2s within the airways may provide an effective therapeutic target for eosinophilic inflammation in airways diseases. Graphical Abstract: Review on Type 2 innate lymphoid cells as important sources of type 2 cytokines in the airways promoting eosinophilic inflammation.